Islamic Accounting as An Information System for Sharia-Based Companies - Desta Puji Fajariani; Hendri Hermawan Adinugraha (Syamilah Publishing, 2024)
This article discusses the importance of Islamic accounting as a source of information for sharia-based companies in the era of globalization and increased awareness of sharia principles. Sharia accounting is based on Islamic sharia principles, such as the prohibition of riba, gharar, and maysir, as well as the principles of accountability, fairness, and truth. Sharia accounting helps companies ensure compliance with Islamic teachings in operations and finances, and provides relevant and transparent information for stakeholders. Despite facing challenges such as cloud computing, blockhain, and artificial intelligence opens up new opportunities in optimizing the efficiency and accuracy of Islamic accounting. This article highlights the importance of a deep understanding of Sharia principles and the utilization of technology in the development of Islamic accounting. Sharia-based companies, such as Islamic banks, Islamic microfinance, institutions, and halal businesses, require accounting information system that are able to accommodate and monitor sharia-compliant transaction. In this context, Islamic accounting plays a central role in decision-making, finance reporting and corporate governance. The system assists companies in providing transparent, fair, and trustworthy financial reports, which are important to stakeholders including investors, customer, and regulators.